PENDAMPINGAN MASYARAKAT DALAM INOVASI PEMBUATAN LAMPU HIAS ESTETIK DARI BAMBU KELURAHAN TONDON MAMULLU - Patadungan, Ellyn; Marniat, Marniat; Ardiyanti, Wilma Dian; Ronal, Marinus (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Making aesthetic lamps from bamboo not only utilizes natural resources in a sustainable manner but also involves community assistance to create a positive impact in the community. The abundance of bamboo resources is the reason for community service activities through training activities carried out in Mamullu Village, Tana Toraja. The mentoring began with skills training for community members, both skilled and inexperienced in bamboo crafts. This training includes techniques for selecting and preparing bamboo, assembling light structures, and installing safe electrical components. In this process, safety and sustainability aspects are emphasized to ensure high-quality and environmentally friendly final products. Sustainability promotion is an important aspect of this assistance, by educating the public about the benefits of using bamboo as a sustainable raw material. This includes an emphasis on reducing carbon footprint and the importance of supporting local industries that are environmentally friendly. By implementing holistic mentoring like this, it is hoped that the community can not only improve their skills in making aesthetic lamps from bamboo but also produce a sustainable positive impact in the social, economic, and environmental aspects around them